1983
DOI: 10.1002/pol.1983.170210415
|View full text |Cite
|
Sign up to set email alerts
|

A study of the photochemical response of o‐nitrobenzyl cholate derivatives in P(MMA‐MAA) matrices

Abstract: Ortho‐nitrobenzyl cholate esters have been successfully used as photosensitive components in solution inhibition deep UV photoresists. The photochemical behavior of a variety of substituted o‐nitrobenzyl cholate derivaties has been examined and resist sensitivity is related to the quantum yield of the reaction. The most efficient system examined is o, o′‐dinitrobenzyl cholate/P(MMA‐MMA), where the quantum yield of photoreaction is 0.2 and resist sensitivity is ca. 150 mJ/cm2 for a 1.5 μm film. The mode of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 5 publications
1
22
0
1
Order By: Relevance
“…Thus, pivalate esters of 57 have release quantum yields in a polymeric matrix of 0.04 and 0.13 in acetonitrile solution, whereas they are much higher for pivalate ester 66 ( Φ = 0.09 in polymer and 0.64 in acetonitrile). 185 Solution-phase quantum yields cannot be directly extrapolated to those of the solid phase, as the available conformations can be quite different. 186 Derivatives of 66 have many other uses, such as the release of biologically active carboxylic acids in plant cells, 187 or on solid support.…”
Section: Nitroaryl Groupsmentioning
confidence: 99%
“…Thus, pivalate esters of 57 have release quantum yields in a polymeric matrix of 0.04 and 0.13 in acetonitrile solution, whereas they are much higher for pivalate ester 66 ( Φ = 0.09 in polymer and 0.64 in acetonitrile). 185 Solution-phase quantum yields cannot be directly extrapolated to those of the solid phase, as the available conformations can be quite different. 186 Derivatives of 66 have many other uses, such as the release of biologically active carboxylic acids in plant cells, 187 or on solid support.…”
Section: Nitroaryl Groupsmentioning
confidence: 99%
“…Introducing the methyl group into the a-position of 2-nitrobenzyl group gives a high quantum yield for the photoreaction [4] . In this study we tried to prepare a positive photoreactive polyimide having higher sensitivity than a previously reported polyimide [2] on the basis of the above data.…”
Section: Synthesismentioning
confidence: 99%
“…Further, Reichmanis and coworkers prepared a series of 2-nitrobenzyl cholates which had substituent groups in the alcohol portion, and they reported that the derivative with methyl groups in the a-position showed a high quantum yield [4].…”
Section: Introductionmentioning
confidence: 98%
“…11 The former contains the silyl group with the o-nitrobenzyl cholate as a dissolution inhibitor. [12][13][14] These photoresists show excellent thermal properties and outstanding oxygen-RIE resistance. This study discusses the free-radical copolymerization of N-substituted maleimides (RMI) [15][16][17][18][19] and comonomers containing the trimethylsilyl group.…”
Section: Introductionmentioning
confidence: 99%